Decolonization Is Not a Dinner Party: Claudia Jones, China's Nuclear Weapons, and Anti-Imperialist Solidarity. (1st July 2019) - Liu, Zifeng
Abstract : This article examines Claudia Jones's view on nuclear weapons and her attempts in the West Indian Gazette and Afro-Asian Caribbean News and Renmin Ribao to link Beijing's nuclear project to global anti-imperialist and nationalist movements. In hailing China's first successful nuclear test as a major advancement in the international struggle against U.S. empire, Jones underscored the overlaps between her internationalist politics and Beijing's militant foreign policy pronouncements to drive home the need for intensified resistance against imperialism and for national liberation. In this way she also rejected the Soviet doctrine of peaceful coexistence and articulated a peace politics that emphasized the dismantling of imperialism and colonialism as the prerequisite for lasting peace. Her journalistic efforts to wage a global decolonial struggle culminated in her reporting on her 1964 visit to China, where she found "evidence" for Beijing's anti-imperialist commitments. Although she constructed romanticizing, if not entirely counterfactual, narratives of Chinese socialism that corresponded to the party-state's geopolitical and domestic aspirations, she downplayed the implications of the deepening Sino-Soviet Split, thereby formulating a relatively independent position that differed from Beijing's line. Jones's activism around the issue of nuclear weapons, as well as its inconsistencies and contradictions, exemplified the hard work that Black internationalists had to put into forging transnational solidarities and tilting the global geopolitical balance in the favor of the decolonizing world.